Sistem Pakar Diagnosis Hama dan Penyakit Tanaman Hortikultura dengan Teknik Inferensi Forward dan Backward Chaining - Ginanjar Wiro Sasmito (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2017)
One of the obstacles to doing cultivation of horticulture plant is to overcome pest and disease. Pest and disease attack can decrease productivity and even causes harvest fail that influence toward one of income sources in the country. Therefore the diagnose on pest and disease must be done fastly and accurately. One of horticulture plant is red onion and chili plant. An expert system is offered as the second choice after expert on consultation. Using Expert System Development Life Cycle (ESDLC) method, combination inference engine and backward chaining for diagnosing pest and horticulture plant disease created as giving the solution. The technique of reasoning used in this research is rule-based. The result of the research is an application that can be used to diagnosis pest and disease horticulture plant, that are red onion and chili. By this application, the farmer can determine quick action should be taken if the farm pests and diseases, without waiting for a consultation with an expert to do the handling. The application result also could be a learning system to the farmer about pest and disease horticulture plant.